Maksimasi Penjualan dengan Mengoptimalkan UMKM Jus Legarsi dalam Linear Programing - Liebe Liora Sinulingga, Griveny; Evlyn Paskarani Surbakti, V.; Ediana Putri Sembiring, Nesya; Marhiyah, Ainun (Green Publisher Indonesia, 2024)
Micro, Small, and Medium Enterprises (MSMEs) have increasingly become a popular choice for young entrepreneurs, especially in light of limited job opportunities. However, many MSMEs face difficulties in optimizing their production due to limited resource, witch hiders their growth. Kedai Jus Legarsi, a juice business run by Mr.Arie, is one such example, relying heavily on daily customer orders without a strategic production plan. This study aims to analze the challeges feced ny kedai jus Legarsari and proposes solutions through the application of linear programming, to optimize juice production and maximize profits. By examining 12 different juice variants, this research develops an optimization model to help increase productivity and profitability while managing limited raw materials and financial resources. The results offer actionable insights for MSMEs looking to streamline operations and achieve sustainable growth.